REED LINK FOR AQUATIC PLANTS OF ARTIFICIAL AND NATURAL POND BODIES (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2025)
This article presents the process of mowing reeds in water bodies using a boat equipped with vertical and horizontal cutting units on a floating reed cutter. The power cable must be insulated and long enough to connect to a nearby electrical panel. The use of electric batteries can also be considered if they are available in large quantities. The working equipment, or unit, is connected to the power grid, and the reeds are mown using a horizontal mower. Since the auxiliary worker is located at the bottom of the reservoir at a depth of 0.4-0.5 m, he easily catches the cut reeds and feeds it to the raft.